Wind Power Potentials in Cameroon and Nigeria: Lessons from South Africa - Mas'ud, A.A.; Wirba, A.V.; Ardila-Rey, J.A.; Albarracín, R.; Muhammad-Sukki, F.; Duque, A.J.; Bani, N.A.; Munir, A.B. (MDPI, 2017)
Wind energy has seen a tremendous growth for electricity generation worldwide and reached 456 GW by the end of June 2016. According to the World Wind Energy Association, global wind power will reach 500 GW by the end of 2016. Africa is a continent that possesses huge under-utilized wind potentials. Some African countries, e.g., Morocco, Egypt, Tunisia and South Africa, have already adopted wind as an alternative power generation source in their energy mix. Among these countries, South Africa has invested heavily in wind energy with operational wind farms supplying up to 26,000 GWh annually to the national grid. However, two African countries, i.e., Cameroon and Nigeria, have vast potentials, but currently are lagging behind in wind energy development. For Nigeria, there is slow implementation of renewable energy policy, with no visible operational wind farms; while Cameroon does not have any policy plan for wind power. These issues are severely hindering both direct foreign and local investments into the electricity sector. Cameroon and Nigeria have huge wind energy potentials with similar climatic conditions and can benefit greatly from the huge success recorded in South Africa in terms of policy implementation, research, development and technical considerations. Therefore, this paper reviews the wind energy potentials, policies and future renewable energy road-maps in Cameroon and Nigeria and identifies their strength and weakness, as well as providing necessary actions for future improvement that South Africa has already adopted.